Spectrophotometric determination of the dissociation constants of fluorescein in micellar media - Niazi, Ali, kemičar (Array, 2009)
Summary: The investigation of the dissociation equilibrium of fluorescein in aqueous micellar solution was determined spectrophotometrically at 25 °C and at ionic strength of 0.1 mol dm−3. For this purpose, the effect of nonionic (TX100), cationic (CTAB) and anionic (SDS) surfactants on the absorption spectra of fluorescein at different pH values were studied. To evaluate the pH-absorbance data, a resolution based on the combination of soft- and hard-modeling is applied. The acidity constants of all related equilibria are estimated using the whole spectral fitting of the collected data to an established factor analysis model. DATAN program was applied for determination of acidity constants. Results show that the pKa values of fluorescein are influenced as the percentages of an anionic and a cationic surfactant such as SDS and CTAB, respectively, are added to the solution of this reagent. Also, neutral surfactant such as TX100 only affects pKa1. Effects of surfactant on acidity constants and pure spectrum of each component are also discussed